Ord og IT - Alfort, Esben (Nordiske Studier i Leksikografi, 2018)
With so many new digital language tools being developed these years, it is easy to fear for the immediate future of traditional lexicography. How-ever, no digital tool can be perfected without lexicographic knowledge being supplied by someone who really understands the way of words. In fact, the need for lexicographic skills has never been greater.